Avaliação dos impactos ambientais da estação de tratamento de esgoto do bairro CPA III – Lagoa Encantada em Cuiabá/MT utilizando indicadores ambientais - Pimpão, Heloisa (2011)
The main objectives of a sewage treatment plant (WWTP) are environmental conservation and protection of health, sometimes the carried through activities inside of the station can generate generate some impact on the environment and neighbors. The aim of this study is to assess the impacts generated by the neighborhood WWTP III CPA Cuiabá/MT, known as the Lagoa Encantada. Initially identified the environmental aspects and impacts of activities undertaken at the station, involving the treatment of sewage itself, environmental education, restoration of degraded areas and physical activities, and then developed a matrix of impact, in order to characterize and identify the impacts more significant. Next, it was defined the environment indicators for these significant impacts in order to verify the magnitude of such impacts. Finally, the indicators have been subjected to a content validation in order to identify among these, which are more expressive. It was identified 11 potential impacts, and 8 negative and three positive. The negative impacts are associated with processes and operations related to sewage treatment. And the positive impacts were allocated to various to the developed diverse activities in the station. Among the environmental set, the second most significant validation of the content was: Efficiency of the system, Index of Solid Waste and Index nuisance caused by odors. Knowledge and understanding of the community with regard to season, is a very important factor and should be more widespread, because many people are unaware that the Lagoa Encantada is a sewage treatment station. This work is an important tool for disseminating information about the WWTP for the community in general and for supporting the manager to identify and act on major issues and optimize the benefits arising from activities at the station.